Pengembangan Buklet Pengolahan Limbah Udang Berbasis Entrepreneurship untuk Peserta Didik SMA: Development of Entrepreneurship Based Booklet on Shrimp Waste Management for High School Students - Fitria Hikmatu Inayah; Bambang Hariyadi; Muhammad Erick Sanjaya (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2019)
Learning process that utilizes the environment as a source of learning enables the process of shaping students’ personality towards more positive atitudes, such as caring the environment, reducing pollution, and increasing students' abilities to be more creative, innovative, and have an entrepreneurial spirit. This study aims to develop learning media in the form of entrepreneurship- based booklet for shrimp waste management for high school students. This research is a development research using ADDIE model. Data obtained from questionnaires given to students and teachers. Small group trials were continued with large group trials performed on students in SMAN 1 and SMAN 2 Tanjung Jabung Barat, and 1 biology teacher at each of these schools. Prior to the trial, product validation is done by material experts and media experts. In the small group trials at SMAN 1 and SMAN 2, the responses were 84% and 81% respectively, both are in the "very good" category. In the large group trial, the responses were 80% and 84% with was in the category of "good" and "very good". The perception of biology teachers in each school were 75% and 77% both were in the "good" category. The entrepreneurship-based shrimp waste management booklet is appropriate to be used as a learning medium on waste recycling materials for high schools.